2021
DOI: 10.1002/srin.202100463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Partitioning and Residual Compressive Stresses on the Lattice Strains of Retained Austenite During Quenching and Isothermal Bainitic Holding in a High‐Silicon Medium‐Carbon Steel

Abstract: The residual compressive stresses and dimensional changes related to the lattice strains of retained austenite (RA) phase in a high‐Si, medium‐carbon steel (Fe‐0.53C‐1.67Si‐0.72Mn‐0.12Cr) are investigated for samples austenitized and quenched for isothermal bainitic transformation (Q&B) in the range 5 s to 1 h at 350 °C. Also, samples are directly quenched in water (DWQ) from the austenitization temperature for comparison with Q&B samples. Field emission scanning electron microscopy (FE‐SEM) combined with elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Comparison with experimental measurements. As an advanced high-strength steel, the residual stress of constituents affects not only the mechanical properties 44 but also the dimensional stability 45 of 35CrMo steel. In this study, the 35CrMo steel is quenched for 40 min at 750 °C and tempered for 120 min at 300 °C to obtain the fine strengthened martensitic phase 46 .…”
Section: Multiscale Simulation and Experimental Measurements Of The E...mentioning
confidence: 99%
“…Comparison with experimental measurements. As an advanced high-strength steel, the residual stress of constituents affects not only the mechanical properties 44 but also the dimensional stability 45 of 35CrMo steel. In this study, the 35CrMo steel is quenched for 40 min at 750 °C and tempered for 120 min at 300 °C to obtain the fine strengthened martensitic phase 46 .…”
Section: Multiscale Simulation and Experimental Measurements Of The E...mentioning
confidence: 99%
“…Strength can be achieved by obtaining the multiphase composite structure of high-strength martensite or bainite matrix due to the lath-like structure and high-density lattice defects. [7][8][9] Bhadeshia and Caballero [10][11][12] et al carried out the low-temperature isothermal treatment (above bainite start temperature) for C-Si-Mn steels and found that the slender plates of bainitic ferrite of just 20-40 nm thick were generated, that is, nanostructured bainite or very strong bainite. The excellent mechanical properties with a combination of strength levels exceeding 2000 MPa, hardness at 600-670 HV, and toughness exceeding 30 MPa m 1/2 were achieved.…”
Section: Introductionmentioning
confidence: 99%